Efficacy and safety of tarenflurbil in mild to moderate Alzheimer's disease: a randomised phase II trial. - Wilcock, G; Black, SE; Hendrix, S; Zavitz, K; Swabb, E; Laughlin, M (2008)
BACKGROUND: The amyloid-beta peptide Abeta(42) has been implicated in the pathogenesis of Alzheimer's disease (AD). We aimed to test the effects of tarenflurbil, a selective Abeta(42)-lowering agent (SALA), on cognition and function in patients with mild to moderate AD. METHODS: 210 patients living in the community who had a mini-mental state examination (MMSE) score of 15-26 were randomly assigned to receive tarenflurbil twice per day (400 mg [n=69] or 800 mg [n=70]) or placebo (n=71) for 12 months in a phase II, multicentre, double-blind study. Primary efficacy outcomes were the AD assessment scale cognitive subscale (ADAS-cog), the Alzheimer's Disease Cooperative Study activities of daily living scale (ADCS-ADL), and the clinical dementia rating sum of boxes (CDR-sb). In a 12-month extended treatment phase, patients who had received tarenflurbil continued to receive the same dose, and patients who had received placebo were randomly assigned to tarenflurbil at 800 mg or 400 mg twice per day. Primary efficacy analyses were done by intention to treat. This trial is registered with Health Canada (084527) and the Medicines and Healthcare products Regulatory Agency in the UK (20365/0001/A 69316). FINDINGS: A prespecified interaction analysis revealed that patients with mild AD (baseline MMSE 20-26) and moderate AD (baseline MMSE 15-19) responded differently to tarenflurbil in the ADAS-cog and the ADCS-ADL (p>or=0.10); therefore, these groups were analysed separately. Patients with mild AD in the 800 mg tarenflurbil group had lower rates of decline than did those in the placebo group in activities of daily living (ADCS-ADL difference in slope 3.98 [95% CI 0.33 to 7.62] points per year, effect size [reduction from placebo decline rate] 46.4%, Cohen's d 0.45; p=0.033) and global function (CDR-sb difference -0.80 [-1.57 to -0.03] points per year, effect size 35.7%, Cohen's d 0.42; p=0.042); slowing of cognitive decline did not differ significantly (ADAS-cog difference -1.36 [-4.07 to 1.36] points per year, effect size 33.7%, Cohen's d 0.20; p=0.327). In patients with moderate AD, 800 mg tarenflurbil twice per day had no significant effects on ADCS-ADL and ADAS-cog and had a negative effect on CDR-sb (-52%, Cohen's d -1.08; p=0.003). The most common adverse events were diarrhoea (in seven, nine, and five patients in the 800 mg, 400 mg, and placebo groups, respectively), nausea (in seven, seven, and four patients), and dizziness (in five, nine, and four patients). Patients with mild AD who were in the 800 mg tarenflurbil group for 24 months had lower rates of decline for all three primary outcomes than did patients who were in the placebo group for months 0-12 and a tarenflurbil group for months 12-24 (all p<0.001), and had better outcomes than did patients who were in the placebo group for months 0-12 and the 800 mg tarenflurbil group for months 12-24 (all p<0.05). INTERPRETATION: 800 mg tarenflurbil twice per day was well tolerated for up to 24 months of treatment, with evidence of a dose-related effect on measures of daily activities and global function in patients with mild AD. FUNDING: Myriad Pharmaceuticals.